HAMBATAN DAN TANTANGAN PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Madya Indah Lestari; Sri Sumartiningsih; Erni Suharini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning Social Sciences (IPS) in elementary schools faces various obstacles and challenges, both internal and external. The aim of this research is to identify the obstacles and challenges in IPS learning and to propose strategies to overcome these challenges in the context of the Industrial Revolution 4.0 era. The research method applied is qualitative, using interviews and observations as data collection techniques. The research shows that the main obstacles are internal factors such as student boredom and the variation of learning materials, as well as external factors such as large class sizes and the lack of diversity in teaching methods. Challenges in the Industrial Revolution 4.0 era include curriculum adjustments and improving teacher quality. Strategies that teachers can use include integrating technology into learning, developing student skills, and enhancing teacher professionalism.